INTEGRATED SCIENCE-ISLAMIC CURRICULUM MANAGEMENT STRATEGY - Muhammad Nurhadi; Imam Suprayogo; Mulyono Hadi; Siti Marfuah (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
The dichotomy between science and Islam remains a fundamental issue in Islamic education, necessitating a curriculum management strategy capable of holistically integrating the two. This study aims to analyze the concept, implementation, and implications of an integrated science and Islam curriculum management strategy in realizing graduates with Ulul Albab character at the Faculty of Islamic Studies (FITK) of UIN Maulana Malik Ibrahim Malang. This study uses a qualitative approach with a case study type. Data collection techniques were carried out through in-depth interviews, observation, and documentation studies. Data analysis used the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and conclusion drawing, while data validity was carried out through triangulation of sources and techniques. The results of the study indicate that the curriculum management strategy underwent a transformation from a dichotomous paradigm to a monotheism-based integration through three phases, namely pre-integration, transition, and post-integration which emphasizesembedded integrationbased on Ulul Albab's values ​​and nurturing effect. The curriculum implementation takes place holistically throughvalue-based curriculum, hidden curriculum, digital technology-based learning, RPS integration, Islamic academic culture, Ma'had development, and institutional strengthening based on the Tree of Knowledge paradigm. The implications of curriculum implementation show the formation of Ulul Albab characters through the integration of dhikr, thinking, and good deeds that build spiritual awareness, integrative thinking skills, noble morals, social responsibility, and ethical use of technology. Thus, the integrated curriculum is able to produce graduates who have spiritual depth, breadth of knowledge, noble morals, and professional maturity in an adaptive and sustainable manner according to the demands of contemporary Islamic education, although it still requires systemic strengthening so that its implementation is more equitable and consistent. Keywords: Curriculum Management; Embedded Integration.   Abstract Dikotomi antara sains dan Islam masih menjadi persoalan mendasar dalam pendidikan Islam, sehingga diperlukan strategi manajemen kurikulum yang mampu mengintegrasikan keduanya secara holistik. Penelitian ini bertujuan untuk menganalisis konsep, implementasi, dan implikasi strategi manajmeen kurikulum terintegrasi sains dan Islam dalam mewujudkan lulusan berkarakter Ulul Albab di FITK UIN Maulana Malik Ibrahim Malang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan studi dokumentasi. Analisis data menggunakan model interaktif Miles, Huberman, dan Saldana yang meliputi kondensasi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data dilakukan melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa strategi manajemen kurikulum mengalami transformasi dari paradigma dikotomis menuju integrasi berbasis tauhid melalui tiga fase, yaitu pra-integrasi, transisi, dan pasca-integrasi yang menegaskan embedded integration berbasis nilai dan nurturing effect Ulul Albab. Implementasi kurikulum berlangsung secara holistik melalui value-based curriculum, hidden curriculum, pembelajaran berbasis teknologi digital, integrasi RPS, budaya akademik Islami, pembinaan Ma’had, serta penguatan kelembagaan berbasis paradigma Pohon Ilmu. Implikasi penerapan kurikulum menunjukkan terbentuknya karakter Ulul Albab melalui integrasi dzikir, fikir, dan amal shalih yang membangun kesadaran spiritual, kemampuan berpikir integratif, akhlak mulia, tanggung jawab sosial, serta etika pemanfaatan teknologi. Dengan demikian, kurikulum terintegrasi mampu menghasilkan lulusan yang memiliki kedalaman spiritual, keluasan ilmu, keluhuran akhlak, dan kematangan profesional secara adaptif dan berkelanjutan sesuai tuntutan pendidikan Islam kontemporer, meskipun masih memerlukan penguatan sistemik agar implementasinya lebih merata dan konsisten. Kata kunci: Manajemen Kurikulum; Embedded Integration.